The examiner's effect on the measurement of dissociation and other psychopathological symptoms in college students - Matreno, Joana (2014)
Objective: The aim of this research was to verify if there is a difference in dissociation or other psychopathological symptoms between two groups of college students when questioned by two different examiners. Method: The Dissociative Experiences Scale, the Brief Symptom Inventory and the Marlowe-Crowne Social Desirability Scale were administered to 185 college students in Coimbra. In one group the examiner was of the same age and academic status, while in the other group the examiner was older and a professor. Results: The younger examiner's group scored higher in the Dissociative Experiences Scale and in the Brief Symptom Inventory. There were no differences in the Marlowe-Crowne Social Desirability Scale. Conclusions: The examiner does have an influence in the evaluation of psychopathological symptoms amongst college students and this occurs not because of social desirability, but because of cultural and environmental proximity, age and empathy with the examiner. Implications: The results derived from mental health studies with college students should be interpreted cautiously, and who is the examiner should be pointed out